Preparation and phosphate adsorption performance of La modified bentonite composite membrane - Huan Xi; Xiangming Chang; Tingting Sun; Liang Chen (Frontiers in Materials)
Using selective adsorption membrane for low-concentration phosphate removal from water is one of the current research hotspots. In this study, La modified bentonite PVC membrane (abbreviated as PVC-LaBT) was prepared by chemical precipitation and phase conversion method. Compared to pure PVC membrane and PVC-BT (pure bentonite PVC membrane), PVC-LaBT shows more pores and larger surface roughness, which is due to the intercalation of La ions into the layers of bentonite, resulting in larger pure water flux and adsorption capacity. Using 1 mg·L−1 phosphate solution, after treatment of 8 h by PVC-LaBT, phosphate concentration decreased to 0.1 mg·L−1, significantly less than the phosphate concentrations of solution treated by PVC-BT (0.5 mg·L−1) and PVC (0.7 mg·L−1). At an initial phosphate concentration of 5.0 mg·L−1, the maximum adsorption capacity was measured as 242.86 mg·m−2. Acid solution is conducive to phosphate adsorption, while the phosphate adsorption performance under alkaline solution is poor. Some anions (Cl− and NO3−) have little effects on phosphate adsorption, the others (SO42− and CO32−) can inhibit phosphate adsorption. This study synthesized a green membrane, providing a new strategy for low concentration phosphate removal.